KNOWLEDGE ABOUT MAINTENANCE OF DENTAL AND ORAL HYGIENE USING COUNSELING MEDIA MYSTERY BOX SNAKE LADDER GAME (Study on Class IV and V Student of SD Praja Mukti Surabaya in 2024): PENGETAHUAN TENTANG PEMELIHARAAN KEBERSIHAN GIGI DAN MULUT MENGGUNAKAN MEDIA PENYULUHAN MYSTERY BOX SNAKE LADDER GAME (Studi Pada Siswa Kelas IV dan V SD Praja Mukti Surabaya Tahun 2024) - Kusumaningrum, Nadila (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
One way to improve health is to maintain oral hygiene. The mouth has more functions than just being a way for food to enter, and not many people are aware of the need to maintain oral hygiene. The problem of this research is the high debris index rate for students in grades IV and V at SD Praja Mukti Surabaya, namely 1.96, which is in the bad category. The aim of this research is to determine students' knowledge about maintaining oral hygiene using the mystery box snake ladder game. This type of research is descriptive research. The target of this research was students in grades IV and V of SD Praja Mukti Surabaya, totaling 47 students. The data collection method uses a questionnaire sheet. Results of research on the knowledge of students in grades IV and V of SD Praja Mukti Surabaya regarding maintaining oral hygiene using the mystery box snake ladder game counseling media in the good category.